A dictionary of Asian mythology - Leeming, David Adams, 1937- (Oxford University Press, 2001)
Features stories of revered deities, sacred places, key events and epics, with many recurring themes and traditions. Addresses the key mythologies of the regions we now call India, China, Tibet, Central Asia, Southeast Asia, and Japan; broad overviews of specific cultures and their mythic traditions round out the coverage.